KETERLIBATAN WARGA NEGARA (CIVIC ENGAGEMENT) DALAM NEGARA DEMOKRASI (IMPLEMENTASI DEMOKRASI PANCASILA DI INDONESIA): Indonesia - Nuruddin Nuruddin (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2021)
This study aims to explore in-depth the involvement of citizens in terms of the rights and obligations of citizens constitutionally, as stated in the 1945 Constitution after the amendment. Indonesia is a democratic country, where the highest sovereignty and power rests with the people. This is in accordance with the nature of democracy is a government of the people, by the people, and for the people. Then the state guarantees and provides legal protection to every citizen in implementing their rights and obligations with the principle of equality before the law. As a democratic country, on that basis, the involvement of citizens becomes individual and social awareness in carrying out their participation for the sustainability and continuity of national development in the future based on Pancasila and the 1945 Constitution. The writing of this article is supported by literature studies and national and international research journals that are relevant. The final conclusion is that the forms of citizen involvement include the fields of politics, government, education and science, and technology, social welfare, state defense, religion, and socio-culture. The form of citizen participation above will create conditions for a more advanced nation in the future.